Analisis Komponen Desain Pengembangan Kurikulum Pendidikan Agama Islam di SDN 04 Seluma - Eva Susanti; Desy Eka Citra Dewi (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract: The curriculum design component is still difficult to develop, characterized by still difficulties in planning the curriculum, implementation, development models and evaluating curriculum development. The purpose of the study is to analyze the design components of the curriculum development of Islamic Religious Education in SDN 04 Seluma. Using a qualitative method of analytical approach, using learning tools designed and developed by Islamic Religious Education teachers as a source of information. The results of the study can be concluded that the design of the components of the PAI curriculum development at SDN 04 Seluma has the same tendency as the development of the PAI curriculum in general, the PAI curriculum developed by Islamic religious education teachers has the same tendency as the Hilda Taba curriculum development model, which has stages of experimentation, theory, and application, the content of the PAI curriculum in elementary school includes learning objectives, learning outcomes (CP), Learning Objectives Flow (ATP), teaching methods, learning media. The design component of PAI curriculum development includes five components, namely curriculum development planning components, curriculum development models, curriculum development implementation, and curriculum development evaluation. Thus, it can be suggested, to find out the level of curriculum development, increase the analysis of curriculum design components in schools.Keywords: Analysis, Curriculum Development Design Component, Islamic Religious Education. Abstrak: Komponen desain kurikulum masih sulit dikembangkan ditandai dengan masih sulit merencanakan kurikulum, pelaksanaan, model pengembangan dan kesulitan evaluasi pengembangan kurikulum. Tujuan penelitian untuk menganalisis komponen desain pengembangan kurikulum Penddikan Agama Islam di SDN 04 Seluma. Menggunakan metode kualitatif pendekatan analitik, menggunakan perangkat pembelajaran yang dirancang dan dikembangkan guru Pendidikan Agama Islam sebagai sumber informasi. Hasil penelitian dapat disimpulkan bahwa desain komponen pengembangan kurikulum PAI di SDN 04 Seluma memiliki kecenderungan yang sama dengan pengembangan kurikulum PAI pada umumnya, kurikulum PAI yang dikembangkan guru pendidikan agama Islam memiliki kecenderungan sama dengan model pengembangan kurikulum Hilda Taba, yang memiliki tahapan eksperiment, teori, dan penerapan, isi kurikulum PAI di SD meliputi tujuan pembelajaran, capaian pembelajaran (CP), Alur Tujuan Pembelajaran (ATP), metode ajar, media pembelajaran. Komponen desain pengembangan kurikulum PAI meliputi lima komponen yaitu komponen perencanaan pengembangan kurikulum, model pengembangan kurikulum, pelaksanaan pengembangan kurikulum, dan evaluasi pengembangan kurikulum. Dengan demikian dapat disarankan, untuk mengetahui tingkat pengembangan kurikulum maka tingkatkan analisis komponen desain kurikulum di sekolah.Kata kunci: Analisis, Komponen Desain Pengembangan Kurikulum, Pendidikan Agama Islam.